2016
DOI: 10.1136/bmj.i52
|View full text |Cite
|
Sign up to set email alerts
|

Medical management of renal stones

Abstract: The prevalence of kidney stones is increasing in industrialized nations, resulting in a corresponding rise in economic burden. Nephrolithiasis is now recognized as both a chronic and systemic condition, which further underscores the impact of the disease. Diet and environment play an important role in stone disease, presumably by modulating urine composition. Dietary modification as a preventive treatment to decrease lithogenic risk factors and prevent stone recurrence has gained interest because of its potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
119
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(129 citation statements)
references
References 116 publications
1
119
0
9
Order By: Relevance
“…It has been demonstrated that intake of calcium supplements both with and without meal increases urine calcium, but because of binding of dietary oxalate with calcium when it is taken with meal, the amount of intestinal oxalate absorption and its urine secretion declines and the rate of stone formation would not increase (13). Of note, apart from calcium intake in high amounts, several other dietary habits including low fluid intake, small intake of fruits and vegetable, large sodium intake, excessive consumption of diet rich in oxalate, and high meat intake are involved in stone formation (14). Therefore, patients who are taking calcium and vitamin D supplements should be advised to consider the foregoing predisposing factors of stone formation.…”
Section: Tayebeh Soleymanianmentioning
confidence: 99%
“…It has been demonstrated that intake of calcium supplements both with and without meal increases urine calcium, but because of binding of dietary oxalate with calcium when it is taken with meal, the amount of intestinal oxalate absorption and its urine secretion declines and the rate of stone formation would not increase (13). Of note, apart from calcium intake in high amounts, several other dietary habits including low fluid intake, small intake of fruits and vegetable, large sodium intake, excessive consumption of diet rich in oxalate, and high meat intake are involved in stone formation (14). Therefore, patients who are taking calcium and vitamin D supplements should be advised to consider the foregoing predisposing factors of stone formation.…”
Section: Tayebeh Soleymanianmentioning
confidence: 99%
“…A high prevalence of disease is commonly seen in countries such as Egypt, Saudi Arabia and Pakistan. It is suggested that a high temperature, inadequate fluid intake and low urine volume predispose to stone formation in these areas [10].…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Urinary system stone disease is encountered at a rate of 4-20 % in developed countries [1][2][3][4]. Our country is in the endemic zone for stone disease with an incidence rate of 15 percent [5,6].…”
Section: Introductionmentioning
confidence: 99%